EVALUATION OF MEDICAL WASTE MANAGEMENT BEFORE AND DURING THE COVID-19 PANDEMIC AT SENTRA MEDIKA HOSPITAL CIKARANG - Sholihah, Enny Mar’atus; Sjaaf, Amal Chalik (UI Scholars Hub, 2022)
One of important things in managing Coronavirus Disease 2019 (COVID-19) pandemic is managing medical waste production. Medical waste management start from waste sort until waste manage by licensed parties, both of patients’ waste and health workers’ waste. Sentra Medika Hospital Cikarang is one of the referral hospitals that handles COVID-19. This research is a descriptive analytic study. Researchers analyze hazardous and toxic waste management before and during a pandemic by conducting interviews with the nursing unit and using secondary data. Secondary data was obtained from the hospital environmental health unit. There is no significant differences medical waste before and during pandemic. This happens because there are decreasing of patients amount which come to the hospital. Besides, health services waste is patients waste such as food or drink waste and personal protective equipment such as hazmat, masks, gloves and others. The weight of waste does produce is lighter. Medical waste at Sentra Medika Hospital has been managed in accordance with regulations.